The Arab reawakenig: international responses and implicarions - Hossain, Ishtiaq (2011)
This paper, first of all, argues that the mass uprisings in the Middle East and North Africa (MENA) in 2011 are best described as the “Arab Reawakening.” Then it delves into an explanation of failures of international commentators to predict the uprisings in MENA. In assessing the international responses to the 2011 Arab Reawakening, an attempt would be made to provide an analysis of the motives, and the principles that shaped the responses of the key members of the international community such as the United Nations, the United States, and other members of the North Atlantic Treaty Organisation (NATO); and the Arab League members. Finally, the paper aims to assess the short-term and long-term implications of the 2011 Arab Reawakening.